Humidity controlled sol-gel Zr/TiO2 with optimized band alignment for efficient planar perovskite solar cells. (1st December 2016) - Bu, Tongle; Wen, Min; Zou, Haiyuan; Wu, Junqing; Zhou, Peng; Li, Wangnan; Ku, Zhiliang; Peng, Yong; Li, Qi; Huang, Fuzhi; Cheng, Yi-Bing; Zhong, Jie
Highlights: Humidity controlled sol-gel synthesis. Zr-doping for band alignment. >15% power conversion efficiency with high fill factor of 0.76. Low hysteresis and high stability. Abstract: This work draws attention to environmental influence to function layers interfaces and the band alignment optimization of organic-inorganic metal halide planar perovskite solar cell (PSC), demonstrating an effective route to enhance the PSC photovoltaic conversion efficiency (PCE) and stability. The PCE of the PSC presents a sensitive correlation with the relative humidity (RH) during the electron transport layer (ETL) preparation. Through optimizing the RH condition, the PSCs show outstanding performances using sol-gel TiO2 ETL prepared under 55 RH%. Moreover, we systematically investigate the Zr doping effect in the TiO2 ink with a variation of Zr molar percentages from 0% to 7.5%. A high PCE of 15.06% with a good fill factor of 0.76 is obtained at 2 mol% Zr doping, in contrast to 12.25% of the undoped device. The Mott-Schottky analysis reveals that the elevated open-circuit voltage ( Voc ) is attributed to the upshifting of flat band potential of TiO2 from −4.15 eV to −4.02 eV (vs. vacuum) after doping. Notably, the as-made cell shows low hysteresis and elevated stability with only 15% degradation of PCE (35% for PSC with pyrolyzed TiO2 ) after 550 h/14 RH% ageing without encapsulation.